2014
DOI: 10.2217/pgs.13.230
|View full text |Cite
|
Sign up to set email alerts
|

Full-Gene Sequencing Analysis of NAT2 and its Relationship with Isoniazid Pharmacokinetics in Venezuelan Children with Tuberculosis

Abstract: In Venezuelan children a clear difference in isoniazid pharmacokinetics and acetylator phenotype between genotypically slow and genotypically intermediate or rapid acetylating children was observed. Original submitted 31 July 2013; Revision submitted 11 November 2013.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…1). Unlike the trimodal distribution of isoniazid pharmacokinetics reported in some studies in adults (11,12), the bimodal distribution observed in our study is consistent with other studies in children, in which the pharmacokinetic parameters in those rapid and intermediate genotypes were similar (13,26,27). The bimodal distribution of NAT2 acetylator phenotype in children may be explained by differences in enzyme maturation with age.…”
Section: Discussionsupporting
confidence: 88%
“…1). Unlike the trimodal distribution of isoniazid pharmacokinetics reported in some studies in adults (11,12), the bimodal distribution observed in our study is consistent with other studies in children, in which the pharmacokinetic parameters in those rapid and intermediate genotypes were similar (13,26,27). The bimodal distribution of NAT2 acetylator phenotype in children may be explained by differences in enzyme maturation with age.…”
Section: Discussionsupporting
confidence: 88%
“…Adverse drug reaction is linked to developmental changes of drug metabolism, so it has age-dependent predisposition [33] , [34] , which might explain the different impacts of the GST polymorphisms on the risk of ATHD between children and adults. Indeed, The ontogeny of both NAT and CYP2E1 has been reported in children [35] – [37] , who had a lower metabolism capacity as compared to adults, thereby, reducing the formation of hepatotoxic metabolites produced by NAT and CYP2E1. As a consequence, the detoxification burden is reduced and the impacts of GST polymorphisms on ATHD might be less important in children as compared to adults.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of mutations in N-acetyl transferase 2(NAT2) genes controlling conversion of isoniazid to acetyl-isoniazid in the intestinal and hepatic cells, is well known. A trimodal distribution of isoniazid exposures is described, although in many studies the respective distributions of the apparent clearance for intermediate and rapid metabolizers are not clearly distinguished [71][72][73]. The AUC among slow acetylators is typically 2-to 3-fold greater than in rapid acetylators.…”
Section: Pharmacogenetic Variationmentioning
confidence: 99%